2020
DOI: 10.1038/s41419-020-2434-z
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of lipid metabolism in cancer-associated fibroblasts potentiates migration of colorectal cancer cells

Abstract: Metabolic interaction between cancer-associated fibroblasts (CAFs) and colorectal cancer (CRC) cells plays a major role in CRC progression. However, little is known about lipid alternations in CAFs and how these metabolic reprogramming affect CRC cells metastasis. Here, we uncover CAFs conditioned medium (CM) promote the migration of CRC cells compared with normal fibroblasts CM. CAFs undergo a lipidomic reprogramming, and accumulate more fatty acids and phospholipids. CAFs CM after protein deprivation still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 42 publications
7
109
0
Order By: Relevance
“…For example, activated PSCs showed a remodeled and increased lipid secretome and produced lysophospatidylcholines, which support membrane lipid synthesis, while they were further converted to LPA via autotaxin enzymatic activity to facilitate tumor growth (Auciello et al, 2019). Similarly, CAFs in CRC accumulated fatty acids and phospholipids via an increase in fatty acid synthase (FASN), and were then transferred to cancer cells to induce their migration (Gong et al, 2020).…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…For example, activated PSCs showed a remodeled and increased lipid secretome and produced lysophospatidylcholines, which support membrane lipid synthesis, while they were further converted to LPA via autotaxin enzymatic activity to facilitate tumor growth (Auciello et al, 2019). Similarly, CAFs in CRC accumulated fatty acids and phospholipids via an increase in fatty acid synthase (FASN), and were then transferred to cancer cells to induce their migration (Gong et al, 2020).…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…As in RASFs, lipid metabolism is also shown to play a role in CAFs activation and pathological characteristics. Fatty acids synthase (FASN), a crucial enzyme in fatty acids synthesis, was found to be significantly increased in CAFs, whereas CAF migration was blocked by knockdown of FASN in colorectal cancer [ 93 ]. CAFs are also able to transfer a significant number of proteins and lipids to adjacent cancer cells, thereby contributing to sustain the high proliferation rate of tumor cells.…”
Section: Metabolic Reprogramming As An Alternative Survival Pathwamentioning
confidence: 99%
“…CAFs are also able to transfer a significant number of proteins and lipids to adjacent cancer cells, thereby contributing to sustain the high proliferation rate of tumor cells. Pancreatic stellate cells (PSCs) derived CAFs are shown to secrete abundant lysophosphatidylcholines (LPCs) in the activated fibroblastic state [ 93 ]. Finally, CAFs can produce glutamine, which is shown to increase autophagy of fibroblasts, a potential energy source for promoting the activity of mitochondria in cancer cells.…”
Section: Metabolic Reprogramming As An Alternative Survival Pathwamentioning
confidence: 99%
“…Higher FASN activity in CAF identified its role as FAs supplier in breast cancer (Lopes-Coelho et al, 2018). A recent study using lipidomic profiling showed that CAFs provide fatty acyl, long-chain, and unsaturated FAs for colorectal cancer tumor cell development (Gong et al, 2020). There is still a lack of evidence of lipid synthesis changing CAF phenotypes.…”
Section: Lipid Metabolism In Cancer-associated Fibroblastsmentioning
confidence: 99%